2012
DOI: 10.1111/j.1440-1827.2012.02792.x
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7: A novel tumor endothelial marker in renal cell carcinoma

Abstract: Tumor angiogenesis is necessary for progression and metastasis of solid tumor. Tumor blood vessels are morphologically different from their normal counterparts. In this study, we isolated tumor endothelial cells (TECs) and revealed their abnormalities. We have compared the gene expression profiles of TECs and normal endothelial cells (NECs) by microarray analysis and found that several genes were upregulated in TECs. Expression of the chemokine receptor CXCR7 mRNA was higher in TECs than in NECs. However, info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 42 publications
0
83
1
1
Order By: Relevance
“…Similar results were found in the literature from other tumors such as bladder, pancreas, and kidney. [15,40,41] But is partly different from those available, witch CXCR7 were found primarily in endothelial cells of Fig. 4 a CXCR7, b CXCR4 and c HIF1α mRNA expression according IDH1 mutation status.…”
Section: Discussionmentioning
confidence: 94%
“…Similar results were found in the literature from other tumors such as bladder, pancreas, and kidney. [15,40,41] But is partly different from those available, witch CXCR7 were found primarily in endothelial cells of Fig. 4 a CXCR7, b CXCR4 and c HIF1α mRNA expression according IDH1 mutation status.…”
Section: Discussionmentioning
confidence: 94%
“…It is also expressed at high levels on tumor-associated vasculature and may have an important role in tumor neovascularization [58]. The role of CXCR7 in cell growth/survival was first suggested by the observation that CXCR7-transfected MDA-MB-435 cells expanded more rapidly in culture and they formed larger tumors than controls in an animal model [55,59].…”
Section: Receptor Trio (Cxcr4 Cxcr7 and Cxcr3) In Cancermentioning
confidence: 99%
“…CXCR4 was highly expressed on the more metastatic alveolar RMS (ARMS) cell line whereas CXCR7 was restricted to non-metastatic cells [62]. Like CXCR4, hypoxia is a major inducer of CXCR7 in tumor cells and tumor-associated endothelial cells emphasizing its role in promoting tumor growth as well as angiogenesis in tumors [58]. …”
Section: Receptor Trio (Cxcr4 Cxcr7 and Cxcr3) In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In an animal model of lung cancer, blockage of CXCR7 by its antagonist CCX754 was observed to inhibit tumor growth, suggesting that CXCR7 possesses protumorigenic properties (49). Tumor endothelial cells (TECs) from renal cell carcinoma tissue were used in a previous study that hypothesized that the upregulation of CXCR7 in TECs is a result of tumor microenvironment factors, such as the levels of VEGF (50). Prior studies have indicated that CXCL14 is an inhibitor of the CXCL12-CXCR4 signaling axis, and is downregulated by DNA methylation in prostate (51) and lung cancer (52).…”
Section: Regulation Of CXC Chemokines In Angiogenesismentioning
confidence: 99%